Japan's trial to strengthen tension evoked by the territorial disputes - Bae Bumki (Vostočnaâ Aziâ: fakty i analitika, 2022)
The territorial disputes over Senkaku/Diaoyudao and the Kuril Chain are interrelated from historic, legal and political points of view. Both groups of islands are claimed by Japan, and the US participates in the territorial disputes over them as the 3rd party. Russia and China assert that the Kuril Chain and Senkaku/Diaoyudao are the territories controlled by them. At the global level both states take effort in defying US-Japan alliance and thereby maintaining strategic balances. Japan, which doesn’t preserve status-quo, pursues to strengthen tension in North-East Asia in the framework of US – Japan alliance. The US, participating in Sino-Japanese and Russo-Japanese territorial disputes as the 3rd party, enforces its own initiative policies conductive to its interests to Japan. By the way, based on these intergovernmental relations, territorial disputes in North-East Asia are mutually linked to confrontational aspects of the South China Sea. In this situation of intergovernmental contradiction, the peaceful settlement of territorial disputes should be posed in the framework of multilateral strategic talks, as exemplified by ASEAN-centered institutions.